Autosomal dominant mitochondrial membrane protein‐associated neurodegeneration (MPAN). Issue 7 (13th May 2019) - Gregory, Allison; Lotia, Mitesh; Jeong, Suh Young; Fox, Rachel; Zhen, Dolly; Sanford, Lynn; Hamada, Jeff; Jahic, Amir; Beetz, Christian; Freed, Alison; Kurian, Manju A.; Cullup, Thomas; et al.
Abstract: Background: Mitochondrial membrane protein‐associated neurodegeneration (MPAN) is caused by pathogenic sequence variants in C19orf12 . Autosomal recessive inheritance has been demonstrated. We present evidence of autosomal dominant MPAN and propose a mechanism to explain these cases. Methods: Two large families with apparently dominant MPAN were investigated; additional singleton cases of MPAN were identified. Gene sequencing and multiplex ligation‐dependent probe amplification were used to characterize the causative sequence variants in C19orf12 . Post‐mortem brain from affected subjects was examined. Results: In two multi‐generation non‐consanguineous families, we identified different nonsense sequence variations in C19orf12 that segregate with the MPAN phenotype. Brain pathology was similar to that of autosomal recessive MPAN. We additionally identified a preponderance of cases with single heterozygous pathogenic sequence variants, including two with de novo changes. Conclusions: We present three lines of clinical evidence to demonstrate that MPAN can manifest as a result of only one pathogenic C19orf12 sequence variant. We propose that truncated C19orf12 proteins, resulting from nonsense variants in the final exon in our autosomal dominant cohort, impair function of the normal protein produced from the non‐mutated allele via a dominant negative mechanism and cause loss of function. These findings impact the clinical diagnostic evaluation and counseling. Abstract : Autosomal recessive inheritance has been demonstrated for mitochondrial membrane protein‐associated neurodegeneration (MPAN). Here we provide 3 lines of evidence for autosomal dominant inheritance in a portion of cases: (1) a dominant inheritance pattern in 2 large, non‐consanguineous families; (2) manifestation of MPAN in 2 cases with single de novo pathogenic sequence variants; (3) a preponderance of heterozygous cases with frameshift/premature stop or nonsense variants clustering in the last exon.